DREPTURILE OMULUI ÎN SITUAȚII DE CRIZĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Human Rights in Situations of Crisis.Human rights term, as well as crisis term have a very strong social impact, but they often become very difficult for perception, due to their abstraction, thereby the "human rights" notion can be comprehended in two meanings, a wide one, meaning every right a person has, which is an enormity, and the second meaning that refers to fundamental human rights that are protected by European Convention on Human Rights and by the Universal Declaration of Human Rights too, a meaning to which we will refer in this study.